A phase‐II sequential case‐series study of all patients presenting to four plasma exchange centres with presumed relapsed/refractory thrombotic thrombocytopenic purpura treated with rituximab. (8th April 2015) - Clark, William F.; Rock, Gail; Barth, David; Arnold, Donald M.; Webert, Kathyrn E.; Yenson, Paul R.; Kelton, John G.; Li, Lihua; Foley, Steven R.; members of the Canadian Apheresis Group
Summary The primary objective of this phase II study was to evaluate the efficacy of rituximab in the management of adult patients with physician‐diagnosed presumed thrombotic thrombocytopenic purpura (TTP); relapsed or refractory. We conducted a multicentre study in four Canadian hospital‐based apheresis units. Forty patients with presumed TTP (20 refractory and 20 relapsing) were sequentially enrolled and all received rituximab in a standardized manner. A complete response was documented in 14 of 19 refractory patients by week 8 and 15/16 were alive and in remission at 52 weeks (one patient was lost to follow‐up, one was a non‐responder, and three died). Among relapsing patients, 16/18 had a complete response at week 8 and 18/18 at week 52 (one patient lost to follow‐up and one withdrew). At 1 year, all relapsing and 85% of refractory patients survived. Of 38/40 patients who had ADMATS13 testing at study entry, 13/19 refractory and 10/19 relapsing patients had ADAMTS13 < 10% (typical TTP); whereas 6/19 refractory and 9/19 relapsing cases had ADAMTS13 > 10% (other thrombotic microangiopathy; TMA). Refractory‐typical TTP in contrast to refractory‐other TMA and all relapsing patients treated with plasma exchange and rituximab, were less likely to be responsive and more likely to die or relapse.